Pengaruh persentase campuran kulit kayu gelam (Melaleuca Cajuputi) dan cangkang karet (Hevea Brasiliensi) terhadap karakteristik pembakaran briket - Misbachudin Misbachudin; Raybian Nur (TURBO [Tulisan Riset Berbasis Online], 2020)
Development of alternative energy sources that can be one of the potential to produce energy in overcoming the fuel energy crisis. The availability of a lot of rubber trees and gelam bark waste in the area of South Kalimantan so it needs to be used to be processed as raw material for briquettes. In this research using a mixture of rubber shell briquettes and gelam bark waste by varying the weight percentage of the mixture. Tests carried out by burning the briquette on a heating element, to determine the characteristics of combustion in briquettes which include the time of initial ignition, the length of the combustion process, and the change in mass of the briquette to ashes. The results show the length of time of starting the ignition and the length of time the combustion process has decreased with an increasing percentage of gelam bark mixture that is during 13.7 s with a burning time of 5.54 minutes. This is due to fibrous and brittle gelam wood bark so it is flammable and contains volatile matter. High lignin content in the rubber shell leaves more ash than gelam bark which is equal to 5.75 grKeywords : Rubber shell, gelam bark, briquettes, alternative energy, combustion characteristics.